A NOTE ON LARVAL REARING OF THE EDIBLE CRAB, PORTUNUS PELAGICUS LINNAEUS, AT ENNORE HATCHERY, MADRAS - Raman, K; Srinivasagam, S; Rangaswamy, C P; Krishnan, S; Joseph, K O; Sultana, M (Indian Journal of Fisheries, 2011)
The results of an experiment on hatchery rearing of the blue svtimniing crab, Portunus pelagicus, from berry to second instar stage, conducted at the Ennore hatchery of the CIFR Institute, are reported.